Late Pleistocene Vertebrate, Plant and Insect Remains from the lnnerkip Site, Southwestern Ontario - Churcher, Charles; Pilny, Jerry; Morgan, Alan (Géographie physique et Quaternaire, 1990)
ABSTRACTRemains of white-tailed deer (Odocoileus virginianus), meadow voles (Microtus pennsylvanicus), muskrat (Ondatra zibethicus) and Blanding's turtle (Emydoidea blandingi) have been recovered from a peat deposit exposed on a tributary of the Thames River in southwestern Ontario. Numerous insect fossils, principally Coleoptera, and a variety of plants recovered from the same stratigraphie horizon have permitted a partial reconstruction of a larger community at the site of peat deposition. The plant, vertebrate and invertebrate fossils represent part of an assemblage which existed in. or beside, a small pond. Deposition probably occurred at the end of the Sangamon Interglaciation (Isotope Stage 5e) or during warm Early Wisconsinan interstadial (Isotope Stage 5c or 5a).